Parâmetros térmicos de solidificação e macroestrutura da liga al3%cu3%ni, solidificada direcionalmente sob condições transitórias de extração de calor - CORRÊA, Edinaldo Gomes (2020)
The multicomponent alloy Al3%Cu3%Ni, weight percent, was directionally solidified under transient heat extraction conditions, in order to obtain the cooling curve, the solidification thermal variables, such as the displacement velocity of the isotherm liquidus (VL). ), the cooling rate (Ṫ) and the temperature gradient in front of the isotherm liquidus (GL), as well as the alloy ingot production for analysis of its formation macrostructure. For this purpose, the raw materials, aluminum, copper and nickel, which were melted inside a crucible in an electric oven at an average temperature of 850 ºC, after melting, the liquid metal was poured at a temperature of 750 ° C. ° C in an AISI 304 stainless steel ingot mold, inside the water-cooled, one-way vertical upward solidification device, in which six thermocouples were arranged at positions 10, 15, 30, 50, 70 and 90 mm from the base of the In order to monitor and obtain the solidification parameters, the cooling system was then activated when the thermocouple of the 10 mm position recorded a temperature 10 % higher than the alloy liquidus (TL) temperature. The thermal parameters at the monitored points and the trend curve functions were obtained for each parameter, the ingot and its macrostructure, formed only with well refined columnar grains, with well defined crystallographic directions, but without the occurrence of the Columnar / Transition. Equiaxial (CTE).